(untitled) (FuLiA/UFMG, 2022)
This article analyzes the public announcing of Jornal dos Sports as a space for building representations that served multiple interests. Exploring the possibilities of using advertising and publicity, I emphasize that it is necessary to understand them in their time and space. When choosing advertising and publicity as the object of history, it is necessary to explore the interests that permeate its production, the representations and the possibilities of reading the experience. Thus, while I was analyzing the advertisements I notice that Jornal dos Sports used several strategies to advertise products and services. Advertising on the pages of Jornal dos Sports also shows itself as a space for building representations about society and the sports field in the 1930s and 1940s, in Rio de Janeiro, and more broadly in Brazil.